Experimental study to optimize cold working, aging temperature, and time on the properties of AA6061 tubes: analysis using design of experiment - Mehmood, Arshad; Akhtar, Kareem; Noor, Sahar; Zahir, M. Zeeshan; Ullah, Barkat; Khan, Razaullah; Salah, Bashir; Sajid Ullah, Syed (Frontiers in Materials, 2023)
Studying the relationship between input factors (cold work, aging time, and aging temperature) and output responses (yield, ultimate tensile strength, and elongation) in aluminium alloys is essential for optimizing the manufacturing process, ensuring consistent quality control, and designing new materials with specific mechanical properties. The drawing process was performed by 10KN Draw Bench with Fixed Plug. Aging and quenching are performed in Box type electric furnace and tubes are quenched at 535 ℃. We record the temperature using K-type calibrated thermocouples. We prepared samples for tensile tests using a Wire Cut Machine (ASTM standard E8 (2004)) and tensile tests were conducted on a tensile test Machine Model QSR-100 at Speed of 1.5mm/min (ASTM B557). For the analysis of experimental data, we use DESIGN Expert and Minitab Software. It was revealed that the temperature factor in the aging process is found the most significant factor. The experimental results indicate that aging temperature is the main factor affecting the yield and ultimate tensile strength while the cold work and aging temperature affect the elongation of the alloy. The reduced model developed using DOE can be a useful tool for predicting the mechanical properties of AA6061 tubes within the limits of the factors investigated, and can provide insights into the optimal combination of cold working and precipitation hardening conditions to achieve desired mechanical properties.